Learning through an Aboriginal language: The impact on students’ English and Aboriginal language skills - Usborne, Esther; Peck, Josephine; Smith, Donna-Lee; Taylor, Donald M. (Canadian Journal of Education/Revue canadienne de l'éducation, 2012)
Aboriginal communities across Canada are implementing Aboriginal language programs in their schools. In the present research, we explore the impact of learning through an Aboriginal language on students’ English and Aboriginal language skills by contrasting a Mi’kmaq language immersion program with a Mi’kmaq as a second language program. The results revealed that students in the immersion program not only had stronger Mi’kmaq language skills compared to students in the second language program, but students within both programs ultimately had the same level of English. Immersion programs can simultaneously revitalize a threatened language and prepare students for success in mainstream society. Keywords: Aboriginal language, bilingual education, immersion, language of instruction